Gone missing [compact disc, unabridged] - Castillo, Linda (Castillo, Linda. Kate Burkholder novel., 2012)
Chief of police Kate Burkholder is called upon to assist when an Amish teenager disappears without a trace. When a body turns up and another young girl goes missing, fear spreads through the community like a contagion. Kate delves into the lives of the missing teens and discovers links to cold cases that may go back years. But will she piece together all the parts of this sinister puzzle before it's too late, or will she find herself locked in a fight to the death with a merciless killer?